Tertiary individual prevention improves mental health in patients with severe occupational hand eczema - Breuer, Kristine; John, Swen Malte; Finkeldey, Florence Isabelle; Boehm, D.; Skudlik, Christoph; Wulfhorst, Britta; Dwinger, Christine; Werfel, Thomas; Diepgen, Thomas L.; Schmid-Ott, Gerhard (Journal of the European Academy of Dermatology and Venereology, 2015)
Background Occupational hand eczema (OHE) is associated with impaired health-related quality of life (QoL) and mental distress. Interdisciplinary inpatient rehabilitation measures in the framework of tertiary individual prevention (TIP) offered by the German employers' liability insurance associations include dermatological treatment, education and psychological interventions. Objective To investigate the effects of interdisciplinary inpatient rehabilitation in the framework of TIP on mental health in patients with severe OHE and the relationships between recovery of OHE and improvement of mental health and QoL. Methods A total of 122 patients participated in the study. A test battery consisting of the German versions of the Hospital Anxiety and Depression Scale (HADS-D), the Dermatology Life Quality Index (DLQI), the Short Form Health Survey-36 (SF-36) and the Trier Inventory for the Assessment of Chronic Stress (TICS) was applied at the time of admission (T1) and 3 weeks after dismissal (T2). Severity of hand eczema was assessed with the Osnabrueck Hand Eczema Severity Index (OHSI). Results All parameters improved significantly from T1 to T2. A relationship was established between the improvement of QoL and recovery of OHE, while there was no such relationship between the improvement of mental distress and improvement of OHE. Nonresponders had significantly more cumulative days of sickness at T1. Conclusions Our data underscore the importance of psychological interventions in addition to dermatological treatment in the framework of prevention measures for OHE. These measures should be applied at an early stage of OHE prior to the occurrence of sick leave.